Mechanical properties determination for a hybrid sandwich bar reinforced with steel wire mesh. Issue 1 (December 2020) - Rădoi, A I; Miriţoiu, C M; Bogdan, M; Bolcu, A; Geonea, I
Abstract: In this paper, some new original hybrid sandwich beams were built in this way: the core is made with polypropylene honeycomb and the reinforcement is made with steel wire mesh. The connection between the reinforcement and the core was made with epoxy resin. The aim of this study is to create a beam from classic materials but combined in a way to obtain a new and original structure. The static experimental conditions are characterized by bending loading of the beams and the determination of statically stiffness. The dynamic parameters were determined from the beams free vibrations. The next experimental montage was used: the beams were clamped at one end and were left free at the other end. At the free end, a Bruel&Kjaer accelerometer with 0.04 pC/ms −2 sensitivity was placed. A force was applied at the free end to bend the beams and after bending, the force was cancelled and the beams were left to freely vibrate. From the free vibrations recording, the next mechanical parameters were determined: the eigenfrequency of the first eigenmode, the damping factors per unit mass and per unit length, the loss factor, the dynamic stiffness and the dynamic Young modulus.